Pengaruh pembiasaan shalat dhuha terhadap perilaku prososial peserta didik pada madrasah berbasis pembiasaan keagamaan - Septia Nurhalisa; Fifi Nofiaturrahmah (Al-Liqo: Jurnal Pendidikan Islam, 2026)
Research on the habitualization of Dhuha prayer has been widely conducted; however, most previous studies have focused on learning discipline, morality, or character development in general. Studies specifically examining the relationship between the habitualization of Dhuha prayer and students’ prosocial behavior remain limited. This study aims to analyze the effect of the habitualization of Dhuha prayer on students’ prosocial behavior in a madrasah that emphasizes religious practices. The study employed a quantitative approach with a correlational design. The sample consisted of 58 students selected through simple random sampling. Data were collected through questionnaires and documentation and analyzed using simple linear regression, Product Moment correlation, t-test, F-test, and coefficient of determination. The findings revealed that the habitualization of Dhuha prayer has a positive and significant effect on students’ prosocial behavior, with a t-value of 8.056 and a significance level of 0.000 (p < 0.05). The coefficient of determination (R² = 0.537) indicates a contribution of 53.7%. These findings support habituation theory and social learning theory and provide empirical evidence for the development of religiosity-based character education in madrasah settings.